UJARAN KEBENCIAN DALAM DAKWAH: ANALISIS TENTANG PENGEJAWANTAHAN IDE AMAR MA’RUF NAHI MUNGKAR DI KALANGAN PARA DA’I DI KALIMANTAN TIMUR - Miftahur Ridho (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2018)
Hate speech is among the most vicious problem faced by Muslims in the world. As Muslims are obliged to perform the principle of al amr bi al ma’ruf wa tanhawna anil munkar (commanding right and forbidding evil), what perceived as hate speech sometimes overlaps such basic tenet of Islamic principle of commanding right and forbidding wrong. The aim of this research is therefore twofold. First, it explore the contruction of hate speech among Da’is (Islamic preachers) in traditional Islamic boarding schools in East Kalimantan. And Seccondly, it explores ideal responses toward such practices as perceived by those Da’is. Findings suggest that the construction of hate speeches and ideal responses towerds it, among Da’is in Islamic traditional boarding schools known as pondok pesantrens, is founded mostly upon the principle of potential damage of those hate speech practices.Keywords: Hate speech, Islamic Da’wa, and Da’is in East Kalimantan.